Long-term exposure to ambient fine particles and gastrointestinal cancer mortality in Taiwan: A cohort study. (May 2020) - Guo, Cui; Chan, Ta-Chien; Teng, Yung-Chu; Lin, Changqing; Bo, Yacong; Chang, Ly-yun; Lau, Alexis K.H.; Tam, Tony; Wong, Martin C.S.; Qian Lao, Xiang
Highlights: This is a large cohort study consisting of 385, 650 adults aged ≥18 years in Taiwan. PM2.5 was associated with higher risk of gastrointestinal cancer mortality. PM2.5 was associated with higher risk of liver and colorectal cancers mortality. Abstract: Background: Information on the association between long-term exposure to PM2.5 and gastrointestinal cancer mortality is scarce. Objectives: This study investigated the association between long-term exposure to PM2.5 and deaths from gastrointestinal cancer and its subtypes in adults in Taiwan. Methods: A total of 385, 650 Taiwanese adults (≥18 years old) jointed a standard medical examination program between 2001 and 2014 and were followed up until 2016. Their vital data were obtained from the National Death Registry maintained by the Ministry of Health and Welfare in Taiwan. We estimated the ambient PM2.5 concentration at individual's address utilising a satellite-based spatiotemporal model at a resolution of 1 km 2 . Cox proportional hazard regression model was used to investigate the associations between ambient PM2.5 and deaths from gastrointestinal, stomach, colorectal and liver cancers. Results: We found that each 10 µg/m 3 increase in PM2.5 was associated with an increased hazard risk (HR) of 1.09 (95% confidence interval (CI): 1.03–1.16) and 1.13 (95%CI: 1.02–1.24) in deaths from gastrointestinal and liver cancers, respectively. The association between PM2.5 and death from colorectal cancer was marginally statistically significant [HR: 1.13 (95%CI: 1.00–1.26)]. We did not find significant associations between PM2.5 and mortality from stomach cancer. Conclusions: Long-term exposure to ambient PM2.5 was associated with an increased risk of deaths from gastrointestinal cancers, liver cancer and also potentially colorectal cancer. Air pollution control strategies are necessary to reduce the burden of gastrointestinal cancer.